The Application of Bioinspired Sonar to Cable Tracking on the Seafloor. (11th October 2010) - Brown Brown, Keith Keith; Capus Capus, Chris Chris; Pailhas Pailhas, Yan Yan; Petillot Petillot, Yvan Yvan; Lane Lane, David David
Abstract : Marine mammals have developed highly effective sonar systems for detecting, identifying, and following underwater objects. In this paper we demonstrate that bio-inspired wideband sonar offers great capability for tracking cables on the seafloor. The analysis of biological signals, including dolphin clicks, suggests two approaches. The first is to use a wideband signal, integrating the response of an object over many frequencies. For simple forms, this is known to give access to shape and material information. The second idea is to use intelligent signals designed to elicit information from specific target types. In this paper results are presented from sets of experiments using bio-inspired wideband sonar. The aim of these experiments is to determine the feasibility of tracking small diameter marine communications cables using the wideband responses. Echoes from four different cable types are analysed using a variety of signals. Experiments using bio-inspired pulses illustrate the benefits of using this type of wideband signal for detection and recognition. A strong correspondence between theoretical and experimental echoes is shown.